New Structural Representation and Digital-Analysis Platform for Symmetrical Parallel Mechanisms. (13th May 2013) - Cao, Wenao; Ding, Huafeng; Zi, Bin; Chen, Ziming
Abstract An automatic design platform capable of automatic structural analysis, structural synthesis and the application of parallel mechanisms will be a great aid in the conceptual design of mechanisms, though up to now such a platform has only existed as an idea. The work in this paper constitutes part of such a platform. Based on the screw theory and a new structural representation method proposed here which builds a one-to-one correspondence between the strings of representative characters and the kinematic structures of symmetrical parallel mechanisms (SPMs), this paper develops a fully-automatic approach for mobility (degree-of-freedom) analysis, and further establishes an automatic digital-analysis platform for SPMs. With this platform, users simply have to enter the strings of representative characters, and the kinematic structures of the SPMs will be generated and displayed automatically, and the mobility and its properties will also be analysed and displayed automatically. Typical examples are provided to show the effectiveness of the approach.